INFORMATION AND COMMUNICATION TECHNOLOGIES’ USE EXPERTISE AND THE UTILISATION BY FRUIT VEGETABLE FARMERS IN NIGERIA - Olanrewaju, Khadijat Olaitan; Bamiwuye, Olubunmi; Idris-Adeniyi, Kaothar; Azeez, Sodiq; Afolayan , Aishat (Applied Studies in Agribusiness and Commerce, 2026)
Information and Communication Technologies (ICTs) represent veritable tools for developing farmers’ capabilities in production resource optimisation. The study assessed fruit and vegetable farmers’ expertise and utilisation of ICT for cucumber and watermelon production. Members of the Osun State Exotic Fruit Farmers’ Group were randomly sampled (90 of 102 farmers) for the study. Data were collected using an interview schedule and analysed using descriptive statistics and multivariate regression analysis. Results reveal the farmers’ mean age was 43.8±10.33 years, and two-thirds (66.67%) were male. Low proportions (19.2% and 14.81%) were good and excellent in ICT use expertise, while many (42.96%) were poor. Some (18.89%) explored social media for linking high-value markets, and 16.67% searched online pages or links in learning about artificial pollination. Farmers’ ICT use expertise and extent of utilisation for cucumber and watermelon production purposes were significantly influenced by their familiarity with ICT tools (b = 1.29 and 1.47) and years of ICT use experience (b = 0.09 and 0.16), respectively, at p≤0.05 significance level. Experience and familiarity with ICT usage spurred farmers to greater proficiency and consequent increased utilisation to optimise cucumber and watermelon production. Specialised ICT training should be prioritised for farmers’ capacity building in intervention programmes